Confirmed Severe Maternal Morbidity is Associated With High Rate of Preterm Delivery. Issue 2 (June 2017) - Kilpatrick, S.J.; Abreo, A.; Gould, J.; Greene, N.; Main, E.K.
Abstract : ( Am J Obstet Gynecol 2016;215:233.e1–233.e7) Approximately 2% of all births (50, 000 women) in the United States are affected by severe maternal morbidity (SMM) with this number growing every year. It is not surprising that this increase in SMM mirrors a similar increase in maternal mortality. SMM events include things like hemorrhage ≥4 units, disseminated intravascular coagulation leading to a hysterectomy, sepsis, and critical care unit admission. It is imperative we better understand the risks and develop interventions to help prevent SMM, with the hope of also reducing maternal mortality. In order to achieve this goal, there have been recent efforts to screen for women who suffer SMM and perform a detailed review of these cases. This has been in an effort to better understand the causes of SMM and ultimately prevent poor maternal outcomes. The purpose of this study was to identify the risks factors associated with true SMM including the relationship between SMM and preterm delivery.